Effects of two foliar fertilizers on fruit quality and volatile flavor compounds in Jinhuangjin peach - YANG Xingwang; WANG Zhiqiang; DUAN Chenlei; WANG Yingying; XUE Guihong; PANG Lingzhi; SHI Meng; JI Xiaohao; ZHANG Deyan; WANG Xiaodi; WANG Haibo (Guoshu xuebao, 2025)
[Objective] The cultivation practices for Jinhuangjin peach in Yiyuan County are characterized by family-based operations, with most planting areas being less than 5 acres. The level of mechanization is relatively low, and the average age of fruit farmers exceeds 55 years old. Foliar fertilizer technology is readily adopted in local orchard management, demonstrating high acceptance among fruit farmers. The experiment was carried out to investigate the effects of two foliar fertilizesr on fruit quality and volatile flavor compounds in Jinhuangjin peach in Yiyuan region, so as to provide theoretical reference for enhancing fruit quality and growing efficiency in peach industry in Yiyuan County, Zibo City, Shandong Province. [Methods] In 2023 and 2024, 11-year-old and 4-year-old Jinhuangjin peach trees, a local specialty variety, served as test materials. Three treatments were implemented: amino acid selenium fertilizer (AA-Se), water-soluble silicon fertilizer (WSF-Si), and clear water (control). The aim was to evaluate the impact of these two foliar fertilizers on the fruit quality and volatile flavor compounds of Jinhuangjin peachs. [Results] The results indicated that, compared to the control, foliar application of both types of foliar fertilizers effectively improved the leaf quality, yield per tree, fruit mass and the content and variety of volatile flavor compounds in Jinhuangjin peaches, but had no significant effect on the soluble solids content, the titration acid content or fruit firmness. The AA-Se increased the chlorophyll-a content, carotenoid content, and leaf mass per area from 6.43% to 8.96%, 12.07% to 18.29%, and 4.83% to 27.27%, respectively, compared to the control. The yield per tree increased from 18.95% to 18.96%. The fruit mass per unit increased from 7.39% to 15.54%. The WSF-Si significantly enhanced leaf thickness and mass per area, with leaf thickness increasing from 5.24% to 6.43% and leaf mass per area increasing from 14.92% to 22.73%, compared to the control. The yield per tree increased from 13.00% to 20.18%. The fruit mass increased from 4.76% to 19.51%. A total of 16 volatile flavor compounds were detected in Jinhuangjin peaches, including 6 aldehydes, 6 esters, 2 terpenes, 1 alcohol and 2-Octanone. It was found that there were certain differences in the types of volatile compounds in Jinhuangjin peach fruits between years, but aldehydes were consistently the predominant volatile compounds, with their contents higher than other types, accounting for 47.04% to 83.02% of the total volatile compounds in all samples, with 2-Hexenal, (E)-being the main aldehyde. In the 2023 experiment, the AA-Se and WSF-Si treatments increased the aldehyde contents by 130.35% and 32.38%, respectively, compared to the control, with no significant difference in ester content. Additionally, with the AA-Se treatment, 3 additional volatile compounds were detected (Furfural, 2-Furancarboxaldehyde, 5-methyland γ-Hexalactone) compared to the control; with the WSF-Si foliar fertilizer treatment, 3 additional volatile compounds were detected (Furfural, γ-Hexalactone, and γ-Decalactone) compared to the control. In the 2024 experiment, the AA-Se and WSF-Si treatments increased the aldehyde contents by 25.05% and 40.61%, respectively, compared to the control; the ester content increased by 124.76% and 49.92%, respectively; and the terpene content increased significantly by 16.31% and 11.06%, respectively. Additionally, with the AA-Se treatment, ethyl acetate was detected compared to the control; with the WSF-Si foliar fertilizer treatment, 4 additional volatile compounds were detected ((E, E)-2, 4-Hexadienal, Ethyl acetate and γ-Hexalactone) compared to the control. In the 2023 experiment, only the AA-Se increased the odor activity value (OAV) of fruity and vegetal aromas compared to the control. In the 2024 experiment, both foliar fertilizer treatments significantly increased the OAV of various types of aromas in the fruit, with the AA-Se increasing the OAV of fruity, vegetal, fatty, and sweet aromas by 56.52%, 29.06%, 38.86%, and 91.20%, respectively, compared to the control; and the WSF-Si increased the OAV of fruity, vegetal, fatty, and sweet aromas by 30.70%, 53.72%, 76.41%, and 35.78%, respectively. The comprehensive evaluation using principal component analysis combined with membership function analysis showed that the rankings for comprehensive evaluation in 2023 and 2024 were: amino acid selenium foliar fertilizer (AA-Se), water-soluble silicon fertilizer (WSF-Si), and control. [Conclusion] Application of AA-Se and WSF-Si significantly enhanced the leaf quality in Jinhuangjin peach; increased the yield per tree, fruit mass and the contents of ester and aldehyde volatile substances in the fruit, and imparted a stronger fruity and vegetal-like aroma, thereby improving the overall fruit quality, with AA-Se showing the best effect. Among the treatments, the most effective method was to spray 600-fold AA-Se once every 15 days starting from the end of flowering, for a total of seven applications. Due to the excellent storage and transportation properties of Jinhuangjin peach, which can be stored in cold storage for up to one month, it is essential to fully consider the impact on postharvest ripening when evaluating its volatile flavor compounds. Silicon can enhance plants' resistance to a range of abiotic and biotic stresses and plays a crucial role in their growth under adverse conditions, so that it is hypothesized that water-soluble silicon fertilizers may have even greater application value in orchards prone to drought and high temperatures. The specific impacts await further investigation.